Below-Cloud Aerosol Scavenging by Different-Intensity Rains in Beijing City - Luan, Tian; Guo, Xueliang; Zhang, Tianhang; Guo, Lijun (Journal of Meteorological Research, 2019)
Below-cloud aerosol scavenging process by precipitation is important for cleaning the polluted aerosols in the atmosphere, and is also a main process for acid rain formation. However, the related physical mechanism has not been well documented and clarified yet. In this paper, we investigated the below-cloud PM 2.5 (particulate matter with aerodynamic diameter being 2.5 μm or less) scavenging by different-intensity rains under polluted conditions characterized by high PM 2.5 concentrations, based on in-situ measurements from March 2014 to July 2016 in Beijing city. It was found that relatively more intense rainfall events were more efficient in removing the polluted aerosols in the atmosphere. The mean PM 2.5 scavenging ratio and its standard deviation (SD) were 5.1% ± 25.7%, 38.5% ± 29.0%, and 50.6% ± 21.2% for light, moderate, and heavy rain events, respectively. We further found that the key impact factors on below-cloud PM 2.5 scavenging ratio for light rain events were rain duration and wind speed rather than raindrop size distribution. However, the impacts of rain duration and wind speed on scavenging ratio were not important for moderate and heavy rain events. To our knowledge, this is the first statistical result about the effects of rain intensity, rain duration, and raindrop size distribution on below-cloud scavenging in China.